Gambaran Mikroba Patogen Pada Gorengan Yang Dijual Di Sekitar Jalan Abdul Kadir Kota Makassar - Nardin nardin; Siti Hajar (Prodi D-III Analis Kesehatan niversitas Indonesia Timur, 2020)
Fried food is a snack food that is in great demand by the public, which is easily contaminated with bacteria both because of the behavior of the handler and its storage which is always served openly and the presentation of food that is not clean and does not meet sanitary requirements. This contributes greatly to the incidence of foodborne diseases, where we know that food is one of the media for disease transmission and in the end it becomes a foodborne disease. This study aims to determine the types of pathogenic microbes and the microbial content found in fried snacks. Sampling was done directly, as many as 5 samples. This type of research is a descriptive laboratory observation. From the research data on 5 samples, 2 samples were found to have Escherichia coli bacteria. While Staphylococcus aureus and Salmonella Sp bacteria were not found, but other bacteria such as Providencia Sp, Enterobacter Sp, Sitobacter Diversus and Serrati Sp were found. Keywords: Pathogenic Microbes, snacks, esherichia coli,staphylococcus aureus, salmonella